1974
DOI: 10.1177/00220345740530024401
|View full text |Cite
|
Sign up to set email alerts
|

Production of Levan and Dextran in Plaque In Vivo

Abstract: Frequent eating of small amounts of sucrose for a period of three days resulted in the in vivo accumulation in plaque of about 1% dextran and about 3% levan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
21
0

Year Published

1978
1978
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 6 publications
0
21
0
Order By: Relevance
“…Maximal synthesis of the enzyme(s) was observed at low growth rates, while little activity was produced by cultures grown at high dilution rates in continuous culture (23,47,48). Regulation of fructanase in this manner could have the net effect of allowing fructan reserves to accumulate in plaque during periods of dietary sucrose intake, as has been observed (16,21). Then, at a later time, when exogenous sources of carbohydrate were exhausted, induction of synthesis of fructan hydrolase activity would permit degradation of these polymers in plaque.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…Maximal synthesis of the enzyme(s) was observed at low growth rates, while little activity was produced by cultures grown at high dilution rates in continuous culture (23,47,48). Regulation of fructanase in this manner could have the net effect of allowing fructan reserves to accumulate in plaque during periods of dietary sucrose intake, as has been observed (16,21). Then, at a later time, when exogenous sources of carbohydrate were exhausted, induction of synthesis of fructan hydrolase activity would permit degradation of these polymers in plaque.…”
mentioning
confidence: 77%
“…The actual synthesis and accumulation of fructans by human dental plaque samples in vitro (22) as well as the accumulation of fructans in plaque in vivo in studies with human volunteers fed a diet rich in sucrose have been demonstrated (16). Following a sucrose intake, fructans were shown to accumulate rapidly and the level of keto sugar slowly decreased with time.…”
mentioning
confidence: 98%
“…From a biological standpoint, levan is known as a phytovirulence factor, providing a detoxifying barrier against plant defense compounds (5). It is also involved in dental plaque formation (6) and possesses antitumor activity (7). When attached to the bacterial cell wall, it produces a dense, slimy layer (capsule).…”
Section: Introductionmentioning
confidence: 99%
“…Oligosaccharides produced from levan by levanases are divided into two large groups : one is DFA IV (di-D-fructose 2,6h :2h6-dianhydrous) and the other is linear fructo-oligosaccharide. In addition to the use for the production of oligosaccharide, the levanase was also reported as potentially participating in the dental plaque mechanism in oral environments [14,15].…”
Section: Introductionmentioning
confidence: 99%